Problematic internet use among nursing students - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (2019)
Background: Heavy and prolonged use of internet by undergraduate students can precipitate problematic internet use in the form of internet addiction (IA) which may affect the psychological well-being and quality of life of the students. This study aims to assess the prevalence of IA among nursing students. Methods: A sample of 174 nursing students from International Islamic University Malaysia participated in the study. Internet addiction was assessed using Chen Internet Addiction Scale. Results: The prevalence of IA among students was 33.3% while 12.6% were at higher risk for addiction. No significant differences in terms of gender and other socio-demographic factors were found. IA is significantly higher among students who were using internet for more than 40 hours per week. Conclusions: IA is considerably high among nursing students. Male and female students are equally affected by IA.